Demotivation of Students in Arabic Learning - Ruslan Ruslan; Muhammad Alqadri Burga (Budapest International Research and Critics University, 2022)
The purpose of this study was to analyze the forms of demotivation of students in learning Arabic along with the solutions made by Arabic teachers in dealing with the demotivation of students. This research method is descriptive qualitative. Informants were selected using a purposive sampling technique from an Arabic teacher and several students of the DDI Mangkoso Islamic Boarding School. The data were obtained through observation, interviews, and documentation techniques and then analyzed using descriptive analysis techniques. The results showed that the students of the DDI Mangkoso Islamic Boarding School had five forms of demotivation in learning Arabic, namely: fear, value conflict, lack of freedom, lack of confidence, and boredom. Even some students experience two or more forms of demotivation in learning Arabic in themselves. The solution made by Arabic teachers in dealing with this demotivation is through the application of learning methods that enable students to converse in Arabic, such as exemplary methods, habituation, and labeling object names. This research has implications for the importance of the environment to motivate students in learning Arabic so that they are accustomed to conversing in Arabic without imposing a perfect mastery of Arabic grammar rules.